Importance of the underlying substrate in determining thrombus location in atrial fibrillation: implications for left atrial appendage closure. Issue 15 (9th May 2012) - Mahajan, Rajiv; Brooks, Anthony G; Sullivan, Thomas; Lim, Han S; Alasady, Muayad; Abed, Hany S; Ganesan, Anand N; Nayyar, Sachin; Lau, Dennis H; Roberts-Thomson, Kurt C; Kalman, Jonathan M; Sanders, Prashanthan
Abstract : Context: The left atrial appendage (LAA) has been suggested to be the dominant location of thrombus in atrial fibrillation (AF) and has led to the development of LAA occlusion as a therapeutic modality to reduce stroke risk. However, the patient populations that would benefit most from this therapy are not well defined. Objective: A systematic review was performed to better define subgroups amenable to appendage closure. Data sources: The English scientific literature was searched using Pubmed through to March 1, 2011. Reference lists of relevant and review articles were screened to retrieve additional articles. Study selection: Studies were only included if they described the location of thrombus in left atrium. Case reports and case series describing less than 10 thrombi were excluded. Data extraction: Two reviewers independently extracted data and assessed quality of each study. Results: A total of 34 studies reporting on the location of atrial thrombus in patients with AF were included: 17 in valvular AF, 10 non-valvular AF and 8 in mixed valvular and non-valvular AF. Atrial thrombi were located outside the LAA in 56% (95% CI 53, 60) of valvular AF, 22% (95% CI 19, 25) in mixed cohorts and 11% (95% CI 6, 15) non-valvular AF. In non valvular AF, the studies with higher proportion of thrombi in the left atrial cavity had non-anticoagulated patients and a greater proportion of ventricular dysfunction and history of stroke. Conclusion: The location of atrial thrombus in patients with AF is dependent on the underlying substrate. In valvular AF, more than half the thrombi are located in the left atrial cavity. In the non-valvular AF group, a smaller proportion of thrombi were located outside the appendage. However, in certain subgroups (ie. non anti-coagulated, left ventricular dysfunction or prior stroke) the chances of left atrial cavity thrombus are higher.